2022
DOI: 10.3390/cells11010160
|View full text |Cite
|
Sign up to set email alerts
|

Multifactorial Mechanism of Sarcopenia and Sarcopenic Obesity. Role of Physical Exercise, Microbiota and Myokines

Abstract: Obesity and ageing place a tremendous strain on the global healthcare system. Age-related sarcopenia is characterized by decreased muscular strength, decreased muscle quantity, quality, and decreased functional performance. Sarcopenic obesity (SO) is a condition that combines sarcopenia and obesity and has a substantial influence on the older adults’ health. Because of the complicated pathophysiology, there are disagreements and challenges in identifying and diagnosing SO. Recently, it has become clear that dy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
84
0
15

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 100 publications
(100 citation statements)
references
References 428 publications
(600 reference statements)
1
84
0
15
Order By: Relevance
“…FGF-21 and its receptors such as β-Klotho, FGFR1b, FGFR1c, and FGFR4 are strongly increased in muscle under catabolic conditions ( 61 ). In addition, FGF-21 enhances myoblast differentiation and acts through the FGF-21/SIRT1/AMPK/PGC-1α axis to convert anaerobic myofibers to aerobic ( 11 , 13 ) ( Figure 1 ). FGF-21, as an anti-inflammatory agent, stimulates the oxidation of fatty acids, the production of ketone bodies, and inhibits lipogenesis ( 63 ).…”
Section: Fibroblast Growth Factor-21 (Fgf-21)mentioning
confidence: 99%
See 3 more Smart Citations
“…FGF-21 and its receptors such as β-Klotho, FGFR1b, FGFR1c, and FGFR4 are strongly increased in muscle under catabolic conditions ( 61 ). In addition, FGF-21 enhances myoblast differentiation and acts through the FGF-21/SIRT1/AMPK/PGC-1α axis to convert anaerobic myofibers to aerobic ( 11 , 13 ) ( Figure 1 ). FGF-21, as an anti-inflammatory agent, stimulates the oxidation of fatty acids, the production of ketone bodies, and inhibits lipogenesis ( 63 ).…”
Section: Fibroblast Growth Factor-21 (Fgf-21)mentioning
confidence: 99%
“…FGF-21, as an anti-inflammatory agent, stimulates the oxidation of fatty acids, the production of ketone bodies, and inhibits lipogenesis ( 63 ). FGF-21 is a major regulator of brown fat differentiation by increasing the expression of UCP1 and PGC-1α and thus generates heat in adipose tissue and skeletal muscle ( 11 , 64 ). In confirmation of this, a study reported that suppression of FGF-21 prevents white adipose tissue from turning brown.…”
Section: Fibroblast Growth Factor-21 (Fgf-21)mentioning
confidence: 99%
See 2 more Smart Citations
“…Sarcopenic (loss of muscle mass, often associated with ageing) obesity is the concept that an individual can be meet clinical definitions of obesity (BMI > 30 kg/m 2 ) and simultaneously exhibit skeletal muscle wasting [ 68 , 69 ]. Sarcopenic skeletal muscles are known to be insulin resistant even in the setting of low whole-body fat stores [ 70 ], and considering that skeletal muscle is a primary site of both insulin action and glucose uptake/storage [ 71–75 ], sarcopenia contributes significantly to systemic metabolic syndrome [ 76 ].…”
Section: Obesity's Link To Insulin Resistance and Hyperinsulinemiamentioning
confidence: 99%